2005
DOI: 10.1124/mol.105.011437
|View full text |Cite
|
Sign up to set email alerts
|

2-Cyano-3,12-dioxoolean-1,9-dien-28-oic Acid and Related Compounds Inhibit Growth of Colon Cancer Cells through Peroxisome Proliferator-Activated Receptor γ-Dependent and -Independent Pathways

Abstract: 2-Cyano-3,12-dioxoolean-1,9-dien-28-oic acid (CDDO) and the corresponding methyl (CDDO-Me) and imidazole (CDDOIm) esters induce peroxisome proliferator-activated receptor ␥ (PPAR␥)-dependent transactivation in SW-480 colon cancer cells, and these responses were inhibited by small inhibitory RNA for PPAR␥. Moreover, in a mammalian two-hybrid assay using the PPAR␥ 2 -VP16 fusion plasmid and GAL4-coactivator/ corepressor chimeras and a construct (pGAL4) containing five tandem GAL4 response elements, CDDO, CDDO-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 27 publications
(31 reference statements)
7
79
0
Order By: Relevance
“…This difference in tissue/cell selectivity between CDDO and thiazolidinediones in their PPARg-dependent responses may result from the unique ability of CDDO to recruit different classes of coactivators. As such, our data in colon cancer cells showed recruitment of multiple coactivators (Src-1, Src-2, Src-3, TRAP220/DRIP205, CARM-1, and PGC-1) that is qualitatively different from that induced by other PPARg ligands (41).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This difference in tissue/cell selectivity between CDDO and thiazolidinediones in their PPARg-dependent responses may result from the unique ability of CDDO to recruit different classes of coactivators. As such, our data in colon cancer cells showed recruitment of multiple coactivators (Src-1, Src-2, Src-3, TRAP220/DRIP205, CARM-1, and PGC-1) that is qualitatively different from that induced by other PPARg ligands (41).…”
Section: Discussionmentioning
confidence: 87%
“…Because caveolin-1 exhibits tumor-suppressing and growth-inhibitory activities, these results suggest that the induction of caveolin-1 is important for the antiproliferative effects of PPARg-active CDDO in breast cancer. We have recently reported that CDDOinduced growth inhibition of colon cancer cell correlated with induction of caveolin-1 in PPARg-dependent fashion (41). Further studies will need to be done to determine whether the induction of caveolin-1 by CDDO is responsible for the inhibition of HER2 tyrosine activity and cyclin D1 down-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…44 Another study by Chintharlapalli et al found that CDDO-Im showed higher activity to induce PPARgamma interactions with the corepressor SMRT than CDDO. 45 CDDO induced the transcriptionally active isoform of CEBPA (p42), increased the p42/p30 ratio, and enhanced CEBPA DNA-binding activity ( Figures 3D and 4A-C). Importantly, CDDO partially restored granulocytic maturation of differentiation-arrested BCR/ABL-expressing cells and rescued p42 CEBPA expression from a construct bearing the uORF/spacer region of CEBPA 5ЈUTR.…”
mentioning
confidence: 99%
“…on August 28, 2018. by guest www.bloodjournal.org From CDDO and CDDO-Im have been described earlier. 1,44,45 In a previous report, CDDO-Im but not CDDO induced the monocytic marker CD36, 1,17 suggesting that the CDDO derivatives may induce qualitatively different patterns of myelomonocytic differentiation. In addition, while CDDO acted as a partial agonist for the PPARgamma receptor, another close relative, CDDO-Me, which binds to PPARg with similar affinity, is an antagonist.…”
mentioning
confidence: 99%
“…In addition, they were found to inhibit proliferation, and induce differentiation and apoptosis in cancer cells in vitro. They have also been shown to inhibit carcinogen-induced primary tumor growth, orthotopic and ectopic tumor formation, as well as lung metastasis and in multiple experimental animal models (11,12,(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%